Abnormal Spontaneous Neural Activity in Parkinson’s Disease With “pure” Apathy - Sun, Hai-Hua; Hu, Jian-Bin; Chen, Jing; Wang, Xue-Yang; Wang, Xiao-Li; Pan, Ping-Lei; Liu, Chun-Feng (Frontiers in Neuroscience, 2020)
Background Apathy is one of the most common non-motor symptoms of Parkinson’s disease (PD). However, its pathophysiology remains unclear. Methods We analyzed resting-state functional magnetic resonance imaging (MRI) data acquired at a 3.0T MRI scanner using the amplitude of low-frequency fluctuation (ALFF) metric in 20 de novo, drug-naïve, non-demented PD patients with apathy (PD-A), 26 PD patients without apathy (PD-NA) without comorbidity of depressive or anxious symptoms, and 23 matched healthy control (HC) subjects. Results We found that the ALFF decreased significantly in the bilateral nucleus accumbens, dorsal anterior cingulate cortex (ACC), and left dorsolateral prefrontal cortex in patients with PD-A compared to patients with PD-NA and HC subjects. Furthermore, apathy severity was negatively correlated with the ALFF in the bilateral nucleus accumbens and dorsal ACC in the pooled patients with PD. Conclusion The present study characterized the functional pattern of changes in spontaneous neural activity in patients with PD-A. With the aim to better elucidate the pathophysiological mechanisms responsible for these changes, this study controlled for the potentially confounding effects of dopaminergic medication, depression, anxiety, and global cognitive impairment. The findings of the current study add to the literature by highlighting potential abnormalities in mesocorticolimbic pathways involved in the development of apathy in PD.